(untitled) (World Bulletin of Public Health, 2023)
T1DM and thyroid dysfunction are two of the most common metabolic diseases; the major purpose of this study is to investigate the epidemiologic behavior of T1DM patients who also suffer from thyroid disorders. The study population was represented by 60 type 1 diabetic patients who attended Al-Qadysiyia medical clinic in Al-Diwanyia City, Iraq, from January 2021 to July 2021, with ages ranged 1-16 years, each individual based on diabetes-associated antibodies (assessment of Glutamic acid decarboxylase antibodies, Zinc transport 8 autoantibody and nsulinoma-2 associated autoantibody) and determination of TSH, T3, and T4. Qualitative variables were expressed as absolute frequencies, and relative and quantitative variables as means+SD. The results found patients with diabetes mellitus were found to have TSH levels that were statistically considerably higher than those that are considered normal for healthy individuals, and the prevalence of GADA-Ab, IA-2ic-Ab, and ZnT8-Ab was as follows: 22 (42%), 14 (27%), and 16 (31%), respectively, in pediatric individuals with type 1 diabetes. In conclusion: An significant marker for the diagnosis of type 1 diabetes in children is a low level of thyroid-stimulating hormone in conjunction with the presence of the two autoantibodies (GADA-Ab and ZNT8- Ab).